A Neuroscience Approach to a Virtual Reality (VR) Based Accommodation–Convergence Intervention for Evaluating Intra-Individual Mental Fatigue during Nearwork: A Crossover Experimental Study Concept - Hartono, Riyadi; Pasiak, Taufiq Fredrik; Thadeus, Maria Selvester (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2025)
Introduction: Prolonged nearwork is associated with increased mental fatigue, a neurocognitive state marked by slower processing, reduced accuracy, and diminished executive performance. This condition affects up to 60–70% of students and office workers worldwide. Objective: Analyzing the effect of a VR-based Accommodation–Convergence Intervention on intra-individual mental fatigue parameters during nearwork from a neuroscience perspective. Methods: A crossover experimental study was developed involving 20 healthy male participants (18–25 years) to perform identical 60-minute Pauli test under two conditions: (1) 2D screen-based and (2) 3D VR based (reduce accommodation–convergence by projecting visual object at optical infinity). Mental fatigue was assessed using several biomarkers, including Pauli test performance, P300 amplitude and latency, and EEG Alpha–Theta PSD. Intra-individual differences between conditions were analyzed using a within-subject. The conceptual framework  was supported by a synthesis of 100 peer-reviewed studies (2014–2024) establishing mental fatigue indicators biomarker. Results: Hypothetically, comparisons between 2D screen and 3D VR-based demonstrated improvement in endurance, reflected by a higher Pauli test performance slope, attenuating the increase in P300 latency-amplitude as well as changes in EEG Alpha–Theta indicative of mental fatigue. The results showed a trend of VR exposure across multiple biomarkers, although the confidence intervals were wide in this small-sample pilot study. Conclusion: This study illustrated a neuroscience-based framework demonstrating that accommodation–convergence intervention via VR may influence indicators of mental fatigue. By integrating EEG, P300, and the Pauli test, the approach provides an objective model for assessing intra-individual cognitive endurance.